The effect of inorganic fertilizer and biofertilizer on the growth of patchouli plant (Pogostemon Cablin) - Sytie Syunarti, Muhitam @ Hazri (2008)
The purpose of this research is to study the effect of inorganic fertilizer and biofertilizer to patchouli growth. Fertilizer contain amount of nutrient that need for plant to growth. Different of nutrient in fertilizer give different effect to the growth of Patchouli. DR 2800 spectrophotometer is used to analyze or determination of nitrogen, phosphorus and potassium while boron, zinc, manganese, copper and iron content were done using Atomic Absorption Spectrometry. Harvesting and extraction is started when patchouli is already matured, after 6 month. Oil was extracted using hydro distillation at temperature 100 oC for about 3 hours. Before the extraction, the leaves have to be dried process using oven at temperature 60 oC, overnight. The content of nitrogen, phosphorus and potassium is identified as major component in fertilizer or as main nutrient in the fertilizer then heavy metal. The percentage growth of plant with inorganic were 60%, the percentage of plant with biofertilizer were 58% and the percentage growth of control were 50%. The height and the color number of leaves and the dry weight of plant with inorganic also the highest if comparing with plant treated with biofertilizer and control. But for essential oil and the yield, plant with biofertilizer produce the higher yield with percentage of 0.89 while plant treated with biofertilizer and control, both were 0.88% and 0.48%. As a conclusion, the growth of plant which treated with inorganic was the better but plant which treated with biofertilizer was better in producing essential oil.